A estação arqueológica da Tapada da Venda, Pedroso, Celorico de Basto (Norte de Portugal) : primeiras impressões das escavações de 2001 - Bettencourt, Ana (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This article draws upon the recent archaeological excavations at the site of Tapado da Venda (Celorico de Basto). This site was excavated in the seventies, being the results yet unpublished to date. This is an open settlement site dating to the 2nd millennium BC. This site, which appear to have had short live, was occupied by a farming community.